2014
DOI: 10.2166/wst.2014.516
|View full text |Cite
|
Sign up to set email alerts
|

Degradability of hexachlorocyclohexanes in water using ferrate (VI)

Abstract: Regarding environmental pollution, the greatest public and scientific concern is aimed at the pollutants listed under the Stockholm Convention. These pollutants are not only persistent but also highly toxic with a high bioaccumulation potential. One of these pollutants, γ-hexachlorocyclohexane (γ-HCH), has been widely used in agriculture, which has resulted in wide dispersion in the environment. Remediation of this persistent and hazardous pollutant is difficult and remains unresolved. Of the many different ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…3. It is observed that FeO 4 2− ion in aqueous solution without adding KIO 4 was rapidly decomposed in each temperature ( Fig. 1).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…3. It is observed that FeO 4 2− ion in aqueous solution without adding KIO 4 was rapidly decomposed in each temperature ( Fig. 1).…”
Section: Resultsmentioning
confidence: 90%
“…A set of aqueous K 2 FeO 4 solutions with an initial concentration of 0.55 mmol/L was freshly prepared with/without coexisting KIO 4 of 0.5 mg/ml at 2.57 mol/L NaOH media (the molar ratio of ferrates (VI) vs. KIO 4 is 1:4). The temporal change in FeO 4 2− concentration at different temperatures was measured by UV/vis spectroscopy. The experimental results are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations